Determinación de Helicobacter Pylori en heces por el método inmunocromatogafico y su relación con los factores desencadenantes en los alumnos de la escuela y colegio de la parroquia de Buenavista del cantón Chaguarpamba - Rivera Torres, Fernando David (2014)
Helicobacter pylori affects humans this is the most common chronic and disseminated infections in humans, "gastritis". Infection by Helicobacter pylori is the most common in the world and affects all ages, gender, race or social condition. Research shows that more than 50% of the world population is infected. For that reason this research chose determining Helicobacter pylori in faeces by immunochromatographic method and its relation to the triggers in the students of the school and college at Parroquia Buenavista of the canton Chaguarpamba through descriptive study of cross-section. In this research participated 91 students which met the inclusion criteria and applied a survey to parents to identify triggers. The researcher was able to conclude the following: 41 positive cases representing 45% of the study population, dominate students 4-13 years of age with 71% and in males at 63%. 51% of the population infected with Helicobacter pylori have an income low. Furthermore 68% have piped water service and 10% consume the vital fluid from a natural source. Besides practicing bad hygiene and eating habits as boiling drinking water was detected in 51% of those infected, while 37% do not wash their food before eating. Keywords: Helicobacter pylori, immunochromatographic method, predisposing factors, gastritis.